The Validity of Executed Terms of Settlement in Arbitration, Mediation, Conciliation and in Some Selected Rules of Court - Rabiu, Abdul-Nafiu Mustapha (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)